THE ROLE OF FORENSICS IN THE PROCESS OF PROOF IN CASES OF CRIMES OF AN EXTREMIST - P. Agapov (Теория и практика судебной экспертизы, 2014)
This article examines the main problems associated with the appointment and conductforensic examinations in cases of crimes of an extremist nature based on analysis of thecurrent law and practice.